Moving politics: Emotion and ACT UP’s fight against AIDS - Gould, Deborah B. (University of Chicago Press, 2009)
In the late 1980s, after a decade spent engaged in more routine interest-group politics, thousands of lesbians and gay men responded to the AIDS crisis by defiantly and dramatically taking to the streets. But by the early 1990s, the organization they founded, ACT UP, was no more—even as the AIDS epidemic raged on. Weaving together interviews with activists, extensive research, and reflections on the author’s time as a member of the organization, Moving Politics is the first book to chronicle the rise and fall of ACT UP, highlighting a key factor in its trajectory: emotion. Surprisingly overlooked by many scholars of social movements, emotion, Gould argues, plays a fundamental role in political activism. From anger to hope, pride to shame, and solidarity to despair, feelings played a significant part in ACT UP’s provocative style of protest, which included raucous demonstrations, die-ins, and other kinds of street theater. Detailing the movement’s public triumphs and private setbacks, Moving Politics is the definitive account of ACT UP’s origin, development, and decline as well as a searching look at the role of emotion in contentious politics.
https://transreads.org/wp-content/uploads/2021/07/2021-07-15_60f0412da8a40_deborah-gould-moving-politics-emotion-and-act-ups-fight-against-aids.pdf
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amériques; discipline; identités LGBTQIA2+; militance; périodes historiques; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; thématiques; émotions; états-unis

Des singes, des cyborgs et des femmes : la réinvention de la nature - Haraway, Donna Jeanne (Actes Sud, 2009)
La plus célèbre théoricienne américaine du féminisme analyse à travers des travaux scientifiques qui vont de l'étude des primates à la recherche médicale en passant par la création des cyborgs, l'influence des présupposés culturels, et l'enracinement genré des sciences.
Première publication: 1991
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; approches et analyses; cours; cycles supérieurs; discipline; fem1000; fem7000; féminisme cyborg; genre; identités LGBTQIA2+; lit2815; lit3220; lit3495; premier cycle; périodes historiques; queer; sciences humaines; thématiques; épistémologie

Ni homme ni femme: enquête sur l'intersexuation - Picquart, Julien (La Musardine, 2009)
"Ni homme ni femme est le premier livre, en français et destiné au grand public, à faire le point sur une question quasiment taboue et presque inconnue de la plupart d'entre nous : comment vit-on avec des organes génitaux atypiques ? Pour y répondre, Julien Picquart a rassemblé des témoignages inédits sur le sujet. Quinze personnes racontent leur quotidien, leur parcours, leur vie sentimentale et sexuelle, les traitements hormonaux et chirurgicaux. Les parents témoignent aussi et reviennent sur leurs réactions quand ils ont découvert que leur enfant n'était pas comme les autres. Pour la première fois également, des médecins parlent, de leurs certitudes et de leurs doutes. Toutes ces personnes nous confrontent à leurs interrogations : faut-il ou non opérer ? N'y a-t-il vraiment que deux sexes ? Quelle importance doit-on accorder aux organes génitaux ? Jusqu'où peut aller notre tolérance ? Un ouvrage accessible et profondément humain, qui bouleverse nos certitudes."
Section: 234 pages, 1 page non numérotée ; 19 cm
Keywords: 1900-1999; 1980-1989; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; intersexuation; inégalités; premier cycle; périodes historiques; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques; violences